Grouting material for metal mine

CN122958129APending Publication Date: 2026-10-23KUNMING METALLURGY INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611210005.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

现在一般是采用水泥浆进行灌注,但是水泥浆的导入性能并不好,特别是对于一些大的缝隙,实际上就是空腔,填充效率非常低

Benefits of technology

1.本申请采用两种不同组份进行依次导入,第一导入材料起到筑基作用,填充底部缝隙,第二导入材料则是在能与第一导入材料进行结合的基础上,进行快速成型,起到快速填充以及压迫第一导入材料进入缝隙的作用,且支撑强度能够达到注浆材料的要求。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A kind of metal mine grouting material, comprising first introduction material and second introduction material, the first introduction material includes the following components: cement: 90-110 parts;Nano alumina: 3-5 parts;Lignin sulfonate: 0.5-0.7 parts;Water solid ratio: 4-5;The second introduction material includes the following components: cement: 90-110 parts;Sodium silicate: 4-10 parts;Clay: 1-1.2 parts;Foaming agent: 0.2-0.4 parts;Water solid ratio: 3-4.This application adopts two different components to be introduced in turn, first introduction material plays the role of foundation, fills bottom gap, second introduction material is on the basis of being able to combine with first introduction material, carries out rapid forming, plays the role of rapid filling and compresing first introduction material into gap, and support strength can reach the requirement of grouting material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a grouting material for metal mines. Background Technology

[0002] During metal mining, fissures may be generated. To ensure the safety of the tunneling process, these fissures need to be sealed. Currently, cement grout is commonly used for grouting, but the infiltration performance of cement grout is not good, especially for large fissures that are essentially cavities, resulting in very low filling efficiency. There are two main problems with cement grouting, particularly for large cavity-type fissures: low efficiency and the possibility that the surface of the fissure may be sealed, but the cement grout still hasn't penetrated into the interior. This reduces the filling effect and compromises the foundation support formed by the grouting material. Therefore, it is necessary to improve the grouting materials and process to enhance its effectiveness. Summary of the Invention

[0003] To address the aforementioned problems, this application proposes a grouting material for metal mines, comprising a first introductory material and a second introductory material, wherein the first introductory material comprises the following components: Cement: 90-110 parts; Nano-alumina: 3-5 parts; Lignosulfonate: 0.5-0.7 parts; Water-to-solid ratio: 4-5; The second import material comprises the following components: Cement: 90-110 parts; Sodium silicate: 4-10 parts; Clay: 1-1.2 parts; Foaming agent: 0.2-0.4 parts; Water-to-solid ratio: 3-4. This application uses two different components for sequential introduction. The first introduction material serves as a foundation, filling the bottom gaps. The second introduction material, based on its ability to bond with the first introduction material, is rapidly molded, serving as a rapid filling agent, and its supporting strength meets the requirements of grouting materials.

[0004] Preferably, the second introducing material further includes an inert component, which is rice husk, and the mass fraction of the rice husk is 0.4-0.6 parts.

[0005] Preferably, the rice husks are processed in the following manner: The rice husks are dried in the absence of oxygen at a temperature of 300-400℃ for 0.5-1 h. The material is then crushed and passed through a 50-100 mesh sieve. The material passing through the sieve is used as the rice husk to be added. This application uses thoroughly dried rice husk, which can improve the cement surface, prevent foam breakage, and significantly increase the strength of the second additive material after foaming.

[0006] Preferably, the cement is silicate cement with a grade of 42.5.

[0007] Preferably, the foaming agent is hydrogen peroxide; the hydrogen peroxide is present in an aqueous solution of 60-70 wt%.

[0008] Preferably, use it according to the following steps: The first and second induction materials were prepared by mixing. First, pump the initial injection material into the required grouting space; Then pump in the second introductory material until grouting is complete.

[0009] Preferably, after the first introducing material is pumped in, wait 10-15 minutes before pumping in the second introducing material. This application does not use the method of introducing the second introducing material after curing the first introducing material, mainly for two reasons: first, to avoid delamination of the two layers of materials; and second, to ensure that the introduction of the upper layer of material has a compacting effect on the lower layer of material.

[0010] Preferably, the pumping volume of the first introducing material is not less than 50 wt%. If the mass cannot be estimated, the height of the first introducing material reaching the grouting space is not less than 50%.

[0011] Preferably, the first introducing material is synthesized in the following manner: Cement, nano-alumina, and lignin sulfonate are mixed evenly, and then water is added.

[0012] Preferably, the second introducing material is synthesized in the following manner: Mix cement, sodium silicate, and clay evenly; add foaming agent to water, then mix cement, sodium silicate, and clay evenly and add them to the water containing foaming agent.

[0013] This application can bring the following beneficial effects: 1. This application uses two different components to be introduced sequentially. The first introducing material plays a foundational role and fills the bottom gaps. The second introducing material, based on its ability to bond with the first introducing material, is rapidly formed, which plays a role in quickly filling and compressing the first introducing material into the gaps, and the supporting strength can meet the requirements of grouting materials.

[0014] 2. This application uses thoroughly dried rice husks, which can improve the cement surface, prevent foam breakage, and significantly increase the strength of the second introducing material after foaming.

[0015] 3. This application does not adopt the method of introducing the second material after curing the first material, mainly for two reasons: first, to avoid the two layers of materials from separating; and second, to have a compacting effect on the lower material during the introduction of the upper material. Detailed Implementation

[0016] To clearly illustrate the technical features of this solution, the following detailed description of specific implementation methods will be provided.

[0017] A grouting material for metal mines includes a first introductory material and a second introductory material, wherein the first introductory material comprises the following components: Cement: 90-110 parts; Nano-alumina: 3-5 parts; Lignosulfonate: 0.5-0.7 parts; Water-to-solid ratio: 4-5; The second import material comprises the following components: Cement: 90-110 parts; Sodium silicate: 4-10 parts; Clay: 1-1.2 parts; Foaming agent: 0.2-0.4 parts; Water-to-solid ratio: 3-4.

[0018] The second introducing material also includes an inert component, which is rice husk, with a mass fraction of 0.4-0.6 parts.

[0019] The rice husks are processed in the following manner: The rice husks are dried in the absence of oxygen at a temperature of 300-400℃ for 0.5-1 h. Then crush it, pass it through a 50-100 mesh sieve, and take the sieve-passing material as the rice husk to be added.

[0020] The cement is silicate cement with a grade of 42.5.

[0021] The foaming agent is hydrogen peroxide; the hydrogen peroxide is present in a 60-70 wt% aqueous solution.

[0022] Use it according to the following steps: The first and second induction materials were prepared by mixing. First, pump the initial injection material into the required grouting space; Then pump in the second introductory material until grouting is complete.

[0023] After the first introducing material is pumped in, wait 10-15 minutes before pumping in the second introducing material.

[0024] The pumping volume of the first introducing material shall not be less than 50 wt%. If the mass cannot be estimated, the height of the first introducing material reaching the grouting space shall not be less than 50%.

[0025] The first imported material was synthesized as follows: Cement, nano-alumina, and lignin sulfonate are mixed evenly, and then water is added.

[0026] The second importing material was synthesized as follows: Mix cement, sodium silicate, and clay evenly; add foaming agent to water, then mix cement, sodium silicate, and clay evenly and add them to the water containing foaming agent.

[0027] To demonstrate the validity of this application, the following examples and comparative cases are provided: The following implementation is carried out inside a container with a height of 1000mm and a length and width of 1000mm, with 5 pipes with an inner diameter of 1mm, 5 pipes with an inner diameter of 5mm, and 5 capillary tubes with an inner diameter of 10mm and a length of 200mm reserved at the bottom of the container.

[0028] Example 1: S101. The first introductory material is obtained by mixing and preparation; Mix 90 parts by weight of silicate cement with a grade of 42.5, 3 parts by weight of nano-alumina, 0.5 parts by weight of lignin sulfonate, and 0.4 parts by weight of rice husk evenly. After mixing evenly, add water with a weight of 3 times that of the solid material.

[0029] S102. Mixing and preparing to obtain the second introducing material; Mix 90 parts by weight of silicate cement with a grade of 42.5, 4 parts by weight of sodium silicate, and 1 part by weight of clay evenly; add 0.2 parts by weight of 70wt% hydrogen peroxide aqueous solution as a foaming agent to water with a total weight of 3 times the solid material, and then mix the silicate cement, sodium silicate, and clay evenly into the water containing the foaming agent.

[0030] The rice husks are processed in the following manner: The rice husks were dried in the absence of oxygen at a temperature of 300°C for 1 hour. Then crush it, pass it through a 50-mesh sieve, and take the sieve-passing material as the rice husk to be added.

[0031] S103. First, pump the first injection material into the required grouting space to a height of 500mm; S104. After the first introductory material is pumped in, wait 10 minutes before pumping in the second introductory material until the grouting is completed, and then allow it to cure naturally for 10 days.

[0032] Observe and measure the state of the first introduced material in the capillary: all pipes with an inner diameter of 1 mm, 5 mm, and 10 mm are completely filled and have some outflow. Its compressive strength was measured to be 4.21 MPa.

[0033] Example 2: S201. The first introducing material is obtained by mixing and preparation; Mix 110 parts by weight of silicate cement with a grade of 42.5, 5 parts by weight of nano-alumina, 0.7 parts by weight of lignin sulfonate, and 0.6 parts by weight of rice husk evenly. After mixing evenly, add water with a weight of 4 times that of the solid material.

[0034] S202. Mixing and preparing to obtain the second introducing material; Mix 110 parts by weight of silicate cement with a grade of 42.5, 10 parts by weight of sodium silicate, and 1.2 parts by weight of clay evenly; add 0.4 parts by weight of 60wt% hydrogen peroxide aqueous solution as a foaming agent to water with a total weight of 4 times that of the solid material, and then mix the silicate cement, sodium silicate, and clay evenly into the water containing the foaming agent.

[0035] The rice husks are processed in the following manner: The rice husks were dried in the absence of oxygen at a temperature of 400℃ for 0.5 hours. Then crush it, pass it through a 100-mesh sieve, and take the sieve-passing material as the rice husk to be added.

[0036] S203. First, pump the first injection material into the required grouting space to a height of 500mm; S204. After the first introductory material is pumped in, wait 15 minutes before pumping in the second introductory material until the grouting is completed, and then allow it to cure naturally for 10 days.

[0037] Observe and measure the state of the first introduced material in the capillary: all pipes with an inner diameter of 1 mm, 5 mm, and 10 mm are completely filled and have some outflow. Its compressive strength was measured to be 4.33 MPa.

[0038] Example 3: S301. The first introductory material is obtained by mixing and preparation; Mix 100 parts by weight of silicate cement with a grade of 42.5, 4 parts by weight of nano-alumina, 0.6 parts by weight of lignin sulfonate, and 0.5 parts by weight of rice husk evenly. After mixing evenly, add 3.5 times the weight of water to the solid materials.

[0039] S302. The second introductory material is obtained by mixing and preparation; Mix 100 parts by weight of silicate cement with a grade of 42.5, 7 parts by weight of sodium silicate, and 1.1 parts by weight of clay evenly; add 0.3 parts by weight of 65wt% hydrogen peroxide aqueous solution as a foaming agent to water with a mass of 3 times the weight of the solid materials, and then mix the silicate cement, sodium silicate, and clay evenly into the water containing the foaming agent.

[0040] The rice husks are processed in the following manner: The rice husks were dried in the absence of oxygen at a temperature of 350°C for 0.8 hours. Then crush it, pass it through a 50-mesh sieve, and take the sieve-passing material as the rice husk to be added.

[0041] S303. First, pump the first injection material into the required grouting space to a height of 500mm; S304. After the first introductory material is pumped in, wait 0.8 hours before pumping in the second introductory material until the grouting is completed, and then allow it to cure naturally for 10 days.

[0042] Observe and measure the state of the first introduced material in the capillary: all pipes with an inner diameter of 1 mm, 5 mm, and 10 mm are completely filled and have some outflow. Its compressive strength was measured to be 4.29 MPa.

[0043] Comparative Example 1: Based on Example 1, but using only the first introducing material, and replacing the second introducing material with the first introducing material in the order of Example 1, with other conditions being the same, the state of the first introducing material in the capillary was observed and measured: all the 10mm inner diameter pipes were completely filled and there was some outflow, but the 5mm pipes were about 80% filled and the 1mm pipes were about 50% filled.

[0044] Its compressive strength was measured to be 6.09 MPa.

[0045] Comparative Example 2: Based on Example 1, but using only the second introducing material, and replacing the first introducing material with the second introducing material in the order of Example 1, with other conditions being the same, the state of the first introducing material in the capillary was observed and measured: there was no outflow from any of the pipes with an inner diameter of 1 mm, 5 mm, or 10 mm. Its compressive strength was measured to be 3.59 MPa.

[0046] Comparative Example 3: Based on Example 1, but without using rice husks in S101, and with all other conditions being the same, the state of the first introduced material in the capillary was observed and measured: none of the 5mm and 10mm inner diameter pipes flowed out; however, the 1mm pipe was not filled.

[0047] Its compressive strength was measured to be 4.06 MPa.

[0048] Comparative Example 4: Based on Example 1, but in S101 the rice husks are roasted, that is, in S102, the rice husks are roasted in the absence of oxygen at a roasting temperature of 800°C for 1 hour, with other conditions being the same. The state of the first introduced material in the capillary is observed and measured: all 5mm and 10mm pipes are completely filled and have flowed out; the pipe with an inner diameter of 1mm is neither filled nor has flowed out.

[0049] Its compressive strength was measured to be 4.14 MPa.

[0050] Comparative Example 5: Based on Example 1, but after the first introductory material is pumped in, wait 30 minutes before pumping in the second introductory material until the grouting is completed, and then allow it to cure naturally for 10 days.

[0051] Observe and measure the state of the first introduced material in the capillary: all the 5mm and 10mm inner diameter pipes are completely filled, and there is some outflow in the 5mm and 10mm pipes, but there is no outflow in the 1mm pipe even though it is basically filled. Its compressive strength was measured to be 4.11 MPa.

[0052] The above are merely embodiments of this application and are not intended to limit the scope of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of the claims of this application.

Claims

1. A grouting material for metal mines, characterized in that: It includes a first import material and a second import material, wherein the first import material comprises the following components: Cement: 90-110 parts; Nano-alumina: 3-5 parts; Lignosulfonate: 0.5-0.7 parts; Water-to-solid ratio: 4-5; The second import material comprises the following components: Cement: 90-110 parts; Sodium silicate: 4-10 parts; Clay: 1-1.2 parts; Foaming agent: 0.2-0.4 parts; Water-to-solid ratio: 3-4.

2. The grouting material for metal mines as described in claim 1, characterized in that: The second introducing material also includes an inert component, which is rice husk, with a mass fraction of 0.4-0.6 parts.

3. The grouting material for metal mines as described in claim 2, characterized in that: The rice husks are processed in the following manner: The rice husks are dried in the absence of oxygen at a temperature of 300-400℃ for 0.5-1 h. Then crush it, pass it through a 50-100 mesh sieve, and take the sieve-passing material as the rice husk to be added.

4. The grouting material for metal mines as described in claim 1, characterized in that: The cement is silicate cement with a grade of 42.

5.

5. The grouting material for metal mines as described in claim 1, characterized in that: The foaming agent is hydrogen peroxide; the hydrogen peroxide is present in a 60-70 wt% aqueous solution.

6. The grouting material for metal mines as described in claim 1, characterized in that: Use it according to the following steps: The first and second induction materials were prepared by mixing. First, pump the initial injection material into the required grouting space; Then pump in the second introductory material until grouting is complete.

7. A grouting material for metal mines as described in claim 6, characterized in that: After the first introducing material is pumped in, wait 10-15 minutes before pumping in the second introducing material.

8. A grouting material for metal mines as described in claim 6, characterized in that: The pumping volume of the first introducing material shall not be less than 50 wt%. If the mass cannot be estimated, the height of the first introducing material reaching the grouting space shall not be less than 50%.

9. A grouting material for metal mines as described in claim 1, characterized in that: The first imported material was synthesized as follows: Cement, nano-alumina, and lignin sulfonate are mixed evenly, and then water is added.

10. A grouting material for metal mines as described in claim 1, characterized in that: The second importing material was synthesized as follows: Mix cement, sodium silicate, and clay evenly; add foaming agent to water, then mix cement, sodium silicate, and clay evenly and add them to the water containing foaming agent.